2022
DOI: 10.3390/ani12212964
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Mechanism for Double-Yolked Eggs in the Early Stage of Egg-Laying in Zhedong White Goose–Function of IGF1 and LHR Signaling

Abstract: The cause of double-yolk (DY) egg production in birds is unclear, but it is related to body weight and adiposity. We explored the causes of the high proportion (up to 26%) of DY eggs in the first clutch of Zhedong white geese. We recorded the egg production of Zhedong white geese during the first egg-laying cycle and counted the proportion of DY eggs. We found that 30% of geese had 3 sets of double or triple follicles of the same diameter in the abdomen, which was close to the DY egg rate. In addition, the mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Salamon et al [8] have demonstrated that when the size and position of double-yolked eggs are appropriate, healthy poultry offspring can be hatched, breaking the traditional view that double-yolked eggs cannot be hatched and revealing the possibility of stable inheritance of double-yolked egg performance. Furthermore, Liu et al [9] explored the double-yolked egg trait of Zhedong white goose, and they discovered that the high level of IGF1 in plasma could cause the production of double-yolked eggs. However, the production of double-yolked eggs [10] is governed by a complex regulation mechanism, and there is more than one factor, causing it to remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Salamon et al [8] have demonstrated that when the size and position of double-yolked eggs are appropriate, healthy poultry offspring can be hatched, breaking the traditional view that double-yolked eggs cannot be hatched and revealing the possibility of stable inheritance of double-yolked egg performance. Furthermore, Liu et al [9] explored the double-yolked egg trait of Zhedong white goose, and they discovered that the high level of IGF1 in plasma could cause the production of double-yolked eggs. However, the production of double-yolked eggs [10] is governed by a complex regulation mechanism, and there is more than one factor, causing it to remain obscure.…”
Section: Introductionmentioning
confidence: 99%